The Role of Social Media Marketing Management in Building Brand Awareness : An Empirical Study in the Digital Economy - Abdullah B; Wahyuni Ekasasmita; Irwan Irwan (Yayasan Vifada Cendikia Indonesia, 2025)
Purpose: This study investigates the role of social media marketing management in building brand awareness in the digital economy. Specifically, it examines the influence of effective social media marketing activities on consumer brand recognition and recall across major digital platforms. Research Design and Methodology: This study employed a quantitative approach using a cross-sectional survey design. Data were collected from 200 active social media users who follow brand accounts on platforms such as Instagram, TikTok, Facebook, and YouTube. The sampling technique used purposive sampling, and data were gathered through structured questionnaires. The study examined one independent variable, namely social media marketing management, which consists of content quality, interaction, consistency, and responsiveness, and one dependent variable, namely brand awareness, which includes recognition, recall, top-of-mind awareness, and familiarity. Data analysis techniques included descriptive statistics, validity and reliability tests, and regression analysis. Findings and Discussion: The results indicate that social media marketing management has a positive and significant effect on brand awareness. Effective management of social media activities enhances consumer recognition, recall, and familiarity with brands. In particular, structured content and active interaction were identified as the key factors influencing brand awareness in the digital environment. Implications: This study provides practical insights for organizations and marketers in optimizing social media strategies to strengthen brand awareness in the digital economy. The findings also contribute to the marketing management literature by emphasizing the importance of consistent and interactive digital communication. Future research is recommended to include additional variables and broader samples to obtain more comprehensive results.